Diabetes Mellitus Secondary to Cushing’s Disease - Barbot, Mattia; Ceccato, Filippo; Scaroni, Carla (Frontiers in Endocrinology, 2018)
Associated to important comorbidities that significantly reduce patients’ overall wellbeing and life expectancy, Cushing’s disease (CD) is the most common cause of endogenous hypercortisolism. Glucocorticoid excess can lead to diabetes, and although its prevalence is probably underestimated, up to 50% of patients with CD have varying degrees of altered glucose metabolism. Fasting glycaemia may nevertheless be normal in some patients in whom glucocorticoid excess leads primarily to higher postprandial glucose levels. An oral glucose tolerance test should thus be performed in all CD patients to identify glucose metabolism abnormalities. Since diabetes mellitus is a consequence of cortisol excess, treating CD also serves to alleviate impaired glucose metabolism. Although transsphenoidal pituitary surgery remains the first-line treatment for CD, it is not always effective and other treatment strategies may be necessary. This work examines the main features of diabetes mellitus secondary to CD and focuses on antidiabetic drugs and how cortisol lowering medication affects glucose metabolism.